Economic and Legal Aspects of the Planned Damages Actions for the Breaches of EC Antitrust Law - Elena Isac (Romanian Journal of European Affairs)
This paper investigates the planned damages actions for breaches of EC antitrust law in order to assess their impact on consumer welfare. It first examines the current legal situation and concurs that the European Union needs to regulate damages actions for breaches of EC antitrust law so that a higher number of consumers could be compensated for their losses. This paper then discusses the main legal provisions proposed by the Commission in the Green and in the White paper on damages actions for breaches of EC antitrust law. The analysis of these proposed legal provisions is done using arguments specific to the economic analysis of law. It is demonstrated that most of these proposed legal provisions will enhance consumer welfare but that there are also proposed legal provisions which will damage consumer welfare. The paper concludes that the planned damages actions for breaches of the EC law will be an improvement compared to the current situation. However, the Commission should amend some of the proposed legal provisions in order to help consumers further.